METHODOLOGICAL FUNDAMENTALS OF STUDENTS’ LEARNING ACTIVITIES - Bugriy О. В. (Pedagogy of Higher and Secondary Education, 2022)
The article explains of principles and ways of organizing learning activities of students, revealed the advantage of a systematic approach to the educational proach.